Research on DNS authoritative server’s performance and security - WANG Yao; HU Ming-zeng; YUN Xiao-chun; LI Bin; YAN Bo-ru (Tongxin xuebao)
Comparing with the top-level domains（TLD） such as the root servers,the local authoritative servers were more vulnerable to device failures and malicious attacks.It was described the existence of authoritative servers and presented a novel domain measurement tool named DNSAuth to collect the information of local authoritative servers automatically.Experiments to the real-life authoritative servers were conducted which highlighting three important aspects: the distribution,the geographic location and their impacts on performance and security.According to five representative attributes,the authoritative servers of China Top100 websites were evaluated and the result shows that only 32% of all the servers act better in performance and security.